Pathways of antibiotic use in Bangladesh: Qualitative protocol for the PAUSE study - Rousham, Emily K; Islam, Mohammad Aminul; Nahar, Papreen; Lucas, Patricia Jane; Naher, Nahitun; Ahmed, Syed Masud; Nizame, Fosiul Alam; Unicomb, Leanne (BMJ Open, 2022)
This article was published in the BMJ Open [© Author(s) (or their employer(s)) 2019. Re-use permitted under CC BY. Published by BMJ. ] and the definite version is available at: http://dx.doi.org/10.1136/bmjopen-2018-028215 The Journal's website is at: https://bmjopen.bmj.com/content/9/1/e028215